Strategic data sales to competing firms - Flavio Delbono; Carlo Reggiani; Luca Sandrini (European Commission, Joint Research Centre (JRC), 2021)
The unprecedented access of firms to consumer level data facilitates more precisely targeted individual pricing. We study the incentives of a data broker to sell data about a segment of the market to three competing firms. The segment only includes a share of the consumers in the market around one of the firms. Data are never sold exclusively. Despite the data are particularly tailored to the potential clientele of one of the firms, we show that the data broker has incentives to sell the list to its competitors. Such market outcome is not socially optimal, and a regulator that aims to maximise consumers and social welfare should consider mandating data sharing.
Keywords: D43; K21; L11; L13; L41; L86; M21; M31; 330; data markets; personalised pricing; price discrimination; oligopoly; sellingmechanisms